Building stories in slow tessitura: deinstitutionalization and narratives in research - Koosah, Jana; Moreira, Maria Inês Badaró; Braga-Campos, Florianita Coelho (Saúde e Sociedade, 2019)
Criticisms on the asylum model not only address the existence of the psychiatric hospital, but also, in the case of deinstitutionalization, the structures and places of power that corroborate the lack of life and dignity of the individual. Studies on the challenges of care in liberty and the production of knowledge that emerges from it become indeclinable. In this sense, the article explores the use of narratives in multicentric evaluative research on the repercussion of the De Volta para Casa Program (Back Home Program) in the lives of those who have been beneficiaries for 15 years. From the chosen theoretical-practical framework, the deinstitutionalization, and the profile of the respondents – people who suffered long years of hospitalization – the challenge of the meeting between the beneficiary and the researcher in the production of the narratives was evidenced. Highlighting the movement of contradictions in the course of research has brought to the data writing and construction syntheses of analysis and intervention. It was possible to observe the change of direction with the recognition of oneself and of another, in the authorship of life in relation to the social fabric and shows the importance of questioning the place of power of the researcher concomitant to the choice of a methodological instrumental within the field.